Some emerging opportunities of nanotechnology development for soilless and microgreen farming - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Nik Ibrahim, Nik Nor Liyana; Wayayok, Aimrun; Hashim, Norhayati (MDPI AG, 2021)
Global food demand has increased in tandem with the world’s growing population, prompting calls for a new sustainable agricultural method. The scarcity of fertile soil and the world’s agricultural land have also become major concerns. Soilless and microgreen farming combined with nanotechnology may provide a revolutionary solution as well as a more sustainable and productive alternative to conventional farming. In this review, we look at the potential of nanotechnology in soilless and microgreen farming. The available but limited nanotechnology approaches in soilless farming include: (1) Nutrients nanoparticles to minimize nutrient losses and improve nutrient uptake and bioavailability in crops; (2) nano-sensing to provide real-time detection of p H, temperature, as well as quantifying the amount of the nutrient, allowing desired conditions control; and (3) incorporation of nanoparticles to improve the quality of substrate culture as crop cultivation growing medium. Meanwhile, potential nanotechnology applications in soilless and microgreen farming include: (1) Plant trait improvement against environmental disease and stress through nanomaterial application; (2) plant nanobionics to alter or improve the function of the plant tissue or organelle; and (3) extending the shelf life of microgreens by impregnating nanoparticles on the packaging or other preservation method.